The Effects of MANSA Historical Board Game toward the Students’ Creativity and Learning Outcomes on Historical Subjects - Kesuma, Ameliasari Tauresia; Harun, Harun; Putranta, Himawan; Mailool, Jefri; Kistoro, Hanif Cahyo Adi (European journal of educational research, 2020)
The constraints of history learning in the Indonesia curriculum are the weekly time is only one hour of lessons and the material is quite dense, if delivered with an explanation and discussion the time is not enough. Therefore, it was sought how to get all material delivered and students not bored. Learning this model is done to condition students as a center of learning, increase creativity and learning outcomes, the project undertaken is called the MANSA Historical board game (MANSA is taken from the abbreviation of our school name). In this case, students are asked to create, design their own board game on a different topic for each group. This study aims to determine the differences in learning outcomes and creativity between the control class and the experimental class of students at senior high schools in Salatiga, Indonesia. The research model used is quasi-experimental. The respondents of the research were 35 students in the experimental class and 35 students in the control class, who had the same homogeneity in creativity and learning outcomes. The results showed that the MANSA Historical board game had a significant effect on creativity and student learning outcomes. It is proven that creativity and student-learning outcomes can be increased. As shown by the mean different test results, there was a difference in the creativity of 0.593 and a learning outcome of 4.224 between the control class and the experimental class before and after treatment. The results showed a difference in learning outcomes between the control class and the experimental class. The average learning outcomes of the experimental class are higher than the average learning outcomes of the control class, as well as student creativity.